Krüppel‐like factor 9 was down‐regulated in esophageal squamous cell carcinoma and negatively regulated beta‐catenin/TCF signaling. Issue 3 (16th January 2015) - Qiao, Fan; Yao, Feng; Chen, Ling; Lu, Chengjun; Ni, Yiqian; Fang, Wentao; Jin, Hai
Abstract : Krüppel‐like factor 9 (KLF9) has been found to play suppressive roles in several types of tumor. However, the expression pattern and biological functions of KLF9 in esophageal squamous cell carcinoma (ESCC) are still unknown. In this study, it was found that the expression of KLF9 was significantly down‐regulated in ESCC compared to their adjacent normal esophageal tissues. Meanwhile, the expression of KLF9 was inversely correlated with the clinical features of ESCC patients. Moreover, in the biological function study, KLF9 was further validated to inhibit the growth, migration, and metastasis of ESCC cells in vitro and in vivo. Mechanistically, KLF9 bind with TCF4 and suppressed the beta‐catenin/TCF signaling as well as the expression of its target gene Cyr61. Collectively, our study clarified the function of KLF9 in both ESCC progression and the regulation of beta‐catenin/TCF signaling. © 2015 Wiley Periodicals, Inc.